Adoption intention of photovoltaic solar systems - Filgueira, Álvaro José de Araújo; Lima, Afonso Carneiro; Castelo, José Sarto Freire (Revista de Administração da UFSM, 2022)
Purpose – The research objective is to analyze the influence of key factors contributing to consumers’ purchase intention grid-connected photovoltaic systems among residential energy consumers. Design/methodology/approach – A survey based on Korcaj et al. (2014) was conducted in a major Brazilian city; 209 valid responses were obtained directly. Data was analyzed using structural equation modeling. Findings – Among significant decision influences are environmental, financial, and autarchy benefits onto perceived global benefit and perceived behavioral control construct onto purchase intention; perceived social benefits, however, were not a relevant influence as opposed to previous studies. Research limitations/implications - Weakness of the model's reliability leading to the exclusion of the perceived total cost construct, which in turn could reduce sample bias and increase the reliability of the model and regarding clarity regarding the product “solar photovoltaic energy system”, as no text was used; this could have left questions unanswered due to the lack of knowledge of respondents about solar technology. Practical implications - The high purchasing power and high education level, along with favorable weather and geography, may contribute to promising perspectives for the product. Furthermore, to promote adhesion of the technology in the city there is a need to increase benefits, to reduce perceived technology costs, and to value the importance of solar energy generation among reference groups. Social implications - The analysis of factors influencing the city’s residents’ intentions of to adopt photovoltaic systems favors further promotion of the technology in the city. Originality/value - It contributes to the development of consumer behavior studies regarding the adoption intention of ecologically sustainable technologies, i.e., GCPSs, thus, filling a gap in the literature on consumer behavior for this product.